BDNF/Trk/KCC2 pathway in nicotine withdrawal-induced hyperalgesia - Shi Wenhui; Ding Yonghong; Yu Ailan; Wang Qinghe; Zhang Zongwang; Zhang Li-Cai (Translational Neuroscience, 2015)
Purpose: To investigate the effect of brain-derived neurotrophic factor (BDNF)/tropomyosin receptor kinase (Trk) on potassium chloride cotransporter 2 (KCC2) in rats following nicotine withdrawal and the roles played by BDNF/Trk/KCC2 pathway in nicotine withdrawal-induced hyperalgesia. Methods: Seventy-eight rats were randomly assigned to five groups: control group (n = 12) without any treatment, normal saline group (NS group, n = 12) and nicotine withdrawal group (NW group, n = 30) receiving a subcutaneous injection of saline or nicotine for 7 days, respectively. The NW + dimethyl sulfoxide (DMSO) (n = 12) and NW+ Trk antagonist K252a groups (n = 12) received an intrathecal injection of DMSO (10 μl) and K252a (10 μg/10 μl) for 3 days after nicotine withdrawal, respectively. Nicotine withdrawal was precipitated by subcutaneous injection of nonselective and noncompetitive antagonist of nicotinic acetylcholine receptors mecamylamine. Pain was tested using thermal withdrawal latency (TWL). A Western blot was used to examine the expression of BDNF and KCC2. Results: The TWL was significantly decreased in NW group relative to control and NS groups (P < 0.01). Compared with the NW group, the NW+K252a group manifested a significantly higher latency (P < 0.01). The BDNF expression was increased and KCC2 was decreased in NW group compared with the control group (P < 0.01). K252a reduced KCC2 downregulation. Conclusion: BDNF/Trk signaling may contribute to nicotine withdrawal-induced hyperalgesia via downregulation of KCC2.